Tuberculosis Treatment Outcome at Becho Health Center, Oromia Region, Ilubabor zone, Ethiopia - Negesa, Lemma; Ayana, Daba (Journal of Medical Biomedical and Applied Sciences, 2017)
Background: Tuberculosis (TB) is a serious public health problem in the developing countries. Early diagnosis, effective treatment and continues assessment of treatment outcome are important indicators of TB control. Thus, the main objective of this study was to assess the treatment outcome of tuberculosis at Becho health center from September 1, 2011 to August 30, 2016.Methods: A five-year retrospective cross-sectional study was employed and data were collected through medical record review who registered at Becho health center from September 1, 2011 to August 30, 2016. Finally data were analyzed using SPSS version 16. We presented descriptive analysis of TB treatment outcome.Results: This study revealed that, out of the 212 pulmonary TB patients (115 males and 97 females), 88.2% had successful TB treatment outcome and 11.8% had unsuccessful TB treatment outcome. About 62 smear positive pulmonary tuberculosis patients were registered. The cure rate and treatment success rate was 22.6% and 65.6% respectively treatment success. In the final multivariate logistic model, the numbers of unsuccessful treatment outcome was higher among patients of weight category 30â39.9âkg and smear negative pulmonary TB 29.2% and extra pulmonary TB 28.3% and HIV positive TB patients 3.04% and unknown HIV status TB patients 7% as compared to their respective comparison groups.Conclusion: In this study, high proportion of successful treatment outcome was documented. Therefore emphasis has to be given for patients with high risk of unsuccessful TB treatment outcome and targeted interventions should be carried out.